FOTO PRODUK AMANDA GRIYA KEBAYA DENGAN ELEMEN PENDUKUNG BANGUNAN CAGAR BUDAYA DI YOGYAKARTA - Tyas Afrian; Edial Rusli; Adya Arsita (Institut Seni Indonesia Yogyakarta, 2018)
AbstrakKebaya yang dulu mendapat sorotan sebagai pakaian kuno kini menjadi pakaian yang modern dan modis. Melalui media fotografi fashion, akan menarik apabila baju kebaya modifikasi dapat divisualisasikan dengan latar belakang bangunan cagar budaya di Yogyakarta sebagai elemen pendukung sehingga memberikan kesan tersendiri bagi para penikmat seni. Fotografi fashion dipilih karena mampu menampilkan produk yang dijual. Dalam karya ini, tantangan yang menarik adalah eksekusi dengan menyatukan kebaya yang modern dengan latar pemotretan berupa bangunan cagar budaya di Yogyakarta, terlebih apabila detail kebaya dapat jelas terlihat. Untuk itu, dilakukan serangkaian metode untuk menggali data yaitu observasi, studi pustaka, dan wawancara. Dlam penciptaan karya dilakukan melalui tahapan ini, yaitu kontemplasi, pravisualisasi, persiapan, eksekusi, hingga pascaproduksi. Karya foto produk dari Griya Amanda Kebaya dalam fotografi fashion ini tidak sekadar menampilkan busana secara visual, tetapi terdapat muatan informasi tentang kebaya dan bangunan yang dipakai. Melalui karya-karya ini didapatkan bahwa kebaya yang disandingkan dengan bangunan cagar budaya menjadi lebih menarik dan mudah dalam menyampaikan atau menanamkan brand image kepada audience, sehingga audience tertarik untuk menyewa atau membuat kebaya di Amanda Griya Kebaya. Kata kunci: Amanda Griya Kebaya, kebaya, cagar budaya, fotografi fashion Abstract Product Photography of Amanda Griya Kebaya with Cultural Heritage Buildings in Yogyakarta as Supporting Elements. Kebaya (a traditional Javanese blouse worn by women) which was considered as an old-fashioned dress, now becomes a modern and stylish dress, of course through a long and uneasy journey. With the medium of fashion photography, it will be interesting if the modified kebaya dress can be visualized with the background of cultural heritage buildings in Yogyakarta as supporting elements, so that it will give a certain impression for art enthusiasts. Fashion photography was chosen because it can show the product that will be sold. Fashion photography aims to make the designed dress looks interesting so that people would be eager to buy it. In this project, the challenge to combine the modern kebaya with the background of cultural heritage buildings in Yogyakarta is interesting to be executed, especially if the details of the kebaya can be seen clearly. To answer that challenge, a series of processes was carried out with some methods namely observation, literature review, and also interview. The steps that were carried out in this project were started with the description of the kebaya dress of Amanda Griya Kebaya, contemplation, pra-visualization, preparement, excecution, until post-production. The result came with the photographs of Amanda Griya Kebaya's product with the supporting element of cultural heritage buildings in Yogyakarta. In the implementation, it was not only creating an artwork that shows the dress visually, but also adding a content of information about the kebaya itself and the buildings used as the backgrounds. Through all of the photoworks, it can be concluded that the kebaya dress combined with cultural heritage building is more interesting and it is also easier to communicate or advertise the brand image to the audience, so that the audience will be interested to rent or order kebaya dress in Amanda Griya Kebaya. Keywords: kebaya, cultural heritage buildings, fashion photography, griya